Techno-Economic Optimization of a Low-Temperature Organic Rankine System Driven by Multiple Heat Sources - Dokl, Monika; Kravanja, Zdravko; Čuček, Lidija (Frontiers in Sustainability, 2022)
This study presents the optimization of organic Rankine cycle (ORC) which utilizes low temperature waste heat from the aluminium production process and two low temperature renewable energy sources, solar thermal energy and geothermal energy. As geothermal energy is present at lower temperature level compared to the other two heat sources, two separate ORC cycles are considered. Optimization of the proposed system is performed based on a non-linear programming (NLP) formulation by maximizing the thermodynamic and economic performance of the system. The main variables considered in the model include temperature, pressure, flowrate, mass enthalpy and energy flows of all the streams in the system. To optimize the variables in the system, correlations were developed, which were formulated as NLP models and optimized by minimizing the sum of least squares. The results show that most of the generated power output can be provided by the waste heat, while the lowest by the solar energy due to the relatively low average solar irradiance at considered location. When monthly time periods are considered, the highest electricity production is generated by the working fluid R1245fa in June, and amounts to 830.4 kW from waste heat, 246.5 kW from geothermal energy and 149.4 kW from solar energy. The proposed system is economically feasible for all three studied working fluids and the discount rates of 2 % and higher. The final conclusions indicate that the proposed ORC system utilizing waste heat, geothermal and solar thermal energy, can generate power in a more sustainable way.